QUAD versus cfDNA in an urban population in the second trimester for detection of trisomy 21: a cost sensitivity analysis*. (2nd October 2017) - Crimmins, Sarah; Doyle, Lauren; Slejko, Julia; Kopelman, Jerome N.; Turan, Ozhan
Abstract: Objective : To compare the unit cost of noninvasive prenatal testing (cell-free DNA [cfDNA]) in an urban population who did not have first-trimester screening as a primary screening tool for trisomy 21 (T21) to multiple marker screening (QUAD). Methods : Retrospective study of all QUAD screens performed at a single center from 2013 to 2015. All QUAD screen performed between 15 and 21 weeks were included in the study. Exclusion criteria were patients without anatomy scans or delivery information. Utilizing our population characteristics, we extrapolated to determine the cost of QUAD with additional screening (cfDNA and amniocentesis) versus QUAD for this entire population. Results : 590 QUAD screens were performed during the study time period. After ultrasound correction of gestational age, 5.9% (35) were screen positive. Within this cohort, 51.4% (18) patients underwent cfDNA and 11.4% (4) had invasive testing. No cases of T21 were identified. It would be cost equivalent to offer cfDNA as a primary screen for T21 at less than 360.54 to the entire population regardless of a priori risk status. Invasive procedures were reduced by 55.4%. Conclusions : cfDNA is an acceptable option for second-trimester screening and as a primary screen eliminates the need for multi-step screening preserving valuable healthcare resources.